PERSEPSI PESERTA TERHADAP PENGGUNAAN METODE CERAMAH PADA DIKLAT PENYULUH AGAMA NON PNS ANGKATAN 74 DI BALAI DIKLAT KEAGAMAAN BANJARMASIN TAHUN 2019 - Syaifullah (Balai Diklat Keagamaan Banjarmasin, 2021)
Many methods can be used in learning in a training, one of which is the lecture method. Thelecture method is considered the conventional method and the oldest learning method; however, this method is still effective if used in the right way. The purpose of this study was to determine how participants' perceptions of the lecture method used by the trainers in teachingin the substantive technical training of Non PNS religious instructors’ class 74 in 2019. Thisresearch was a quantitative descriptive study. The population and sample of the study were34 training participants. Data were collected through a structured questionnaire totaling 11items. The data of the research were analyzed using descriptive statistics. The results showedthat the training participants' perceptions of the lecture method were very good, 35.3% saidthey really liked it, 47.1% said they liked it, and 17.6% said they sometimes liked the lecturemethod. The trainers conveyed the learning objectives, 38.2% stated always, 50% statedfrequently, and 11.8% stated sometimes. Delivering the benefits of learning materials, 55.9% stated always, 41.2% stated frequently, and 2.9% stated sometimes. Delivering the scope of learning, 47.1% stated always, 44.1% stated often, and 8.8% stated sometimes. Usinglanguage that is easy to understand, 67.6% states always, 29.4% states often, and 2.5% states sometimes. Complementing the explanation with examples, 58.8% stated always, 38.2% stated frequently, and 2.9% stated sometimes. Bringing out relevant humor, 55.9% stated always, 32.4% stated often, and 11.8% stated sometimes. Repeating key points, 17.6% stated always, 58.8% stated frequently, and 20.6% stated sometimes. Using sound volume and intonation are good, 61.8% stated always, 32.4% stated frequently, and 5.9% statedsometimes. Transition of material delivery from one point to another, 35.3% stated always,47.1% stated often, and 17.6% stated sometimes. Summing up the learning material, 41.2%stated always, 38.2% stated frequently, and 17.6% stated sometimes.